2017
DOI: 10.1097/dbp.0000000000000440
|View full text |Cite
|
Sign up to set email alerts
|

Comorbid Mental Disorders in Fetal Alcohol Spectrum Disorders: A Systematic Review

Abstract: Increased rates of mental disorders in people with FASD are commonly reported. Mental health providers should routinely consider FASD in the diagnosis and management of mental illness and developmental disorders. The quality of the research and precision of comorbidity estimates would be improved by additional studies including people with FASD and non-FASD comparison subjects. Until these studies are available, this review provides the best available estimates of comorbid mental disorders in people with FASD.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

4
94
1
5

Year Published

2019
2019
2021
2021

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 126 publications
(104 citation statements)
references
References 43 publications
4
94
1
5
Order By: Relevance
“…Accordingly, results may be more representative of less severe and covert cases of PAE. Several subjects suffered from psychiatric comorbidities as is typical of PAE (O'Connor & Paley, ; Weyrauch, Schwartz, Hart, Klug, & Burd, ) and ADHD (Jensen, Martin, & Cantwell, ) samples. A few subjects were taking psychotropic medication at time of study, although they were required to abstain from medication on day of scan.…”
Section: Discussionmentioning
confidence: 99%
“…Accordingly, results may be more representative of less severe and covert cases of PAE. Several subjects suffered from psychiatric comorbidities as is typical of PAE (O'Connor & Paley, ; Weyrauch, Schwartz, Hart, Klug, & Burd, ) and ADHD (Jensen, Martin, & Cantwell, ) samples. A few subjects were taking psychotropic medication at time of study, although they were required to abstain from medication on day of scan.…”
Section: Discussionmentioning
confidence: 99%
“…In addition to the broad range of cognitive deficits as described above, children with FASD are at an increased risk of numerous mental health problems, learning disabilities, and specific behavioral disorders (Fryer et al., ; Kingdon et al., ; Popova et al., ; Weyrauch et al., ). One meta‐analysis examined 127 studies and identified 428 comorbidities (i.e., other diagnoses or conditions) that occur in individuals with FASD (Popova et al., ).…”
Section: Cognitive and Behavioral Functioningmentioning
confidence: 99%
“…One meta‐analysis examined 127 studies and identified 428 comorbidities (i.e., other diagnoses or conditions) that occur in individuals with FASD (Popova et al., ). Among those with FASD, the most prevalent comorbid conditions include ADHD, depression, anxiety disorder, posttraumatic stress disorder, oppositional defiant disorder, conduct disorder, receptive language disorder, and expressive language disorder (O'Connor and Paley, ; Pei et al., ; Popova et al., ; Weyrauch et al., ). Furthermore, alcohol‐exposed children have higher rates of psychological disorders in comparison with typically developing children even when matched on age, gender, and socioeconomic status (Fryer et al., ).…”
Section: Cognitive and Behavioral Functioningmentioning
confidence: 99%
See 1 more Smart Citation
“…This contrasts with the traditional categorical approach to conceptualizing NDDs in which each diagnosis is considered a discrete and separate entity, and intervention occurs when impairment exceeds diagnostic thresholds. A transdiagnostic, dimensional approach to developmental risk aligns with the National Institute of Mental Health Research Domain Criteria framework (Casey, Oliveri, & Insel, ), and is supported by findings of high prevalence of co‐occurrence between NDDs (Weyrauch, Schwartz, Hart, Klug, & Burd, ); overlap among core symptoms of NDDs (Craig et al., ; Dajani, Llabre, Nebel, Mostofsky, & Uddin, ); and marked heterogeneity in behavioral presentation within diagnostic groups, including within monogenic disorders (e.g., Dajani et al., ). This transdiagnostic or cross‐syndrome approach to identifying NDDs lends itself to a model for early intervention in which intervention is targeted at a specific phenotype or a hypothesized shared underlying mechanism, rather than at a diagnostic group.…”
mentioning
confidence: 97%